How Instagram Influencers Contribute to Consumer Travel Decision: Insights from SEM and fsQCA - Wen-Kuo Chen; Pantas H. Silaban; Widya Elisabeth Hutagalung; Andri Dayarana K. Silalahi (Emerging Science Journal, 2023)
In recent years, social media influencers (SMIs) have become independent entities capable of influencing their audiences. Businesses look towards SMIs on Instagram as a marketing communication tool due to their popularity and effectiveness. In tourism, few studies investigate the role of SMI in influencing travel behaviors. The study examines how SMI can influence Instagram followers' travel behaviors. This study determined SMI based on attractiveness, similarity, and expertise. SMI can generate parasocial interactions with followers and build trust by promoting destinations based on these three dimensions. This study tested the research hypothesis on 364 respondents using a dual-approach analysis of structural equation modeling and fuzzy set qualitative comparative analysis. The results of the SEM analysis confirm that consumers were more likely to trust SMI based on their expertise and similarity. Also, this study demonstrated that highly attractive SMI and similarity with followers can lead to parasocial interactions. When consumers trust and feel parasocial interaction with SMI, they are more likely to consider traveling. FsQCA results confirm the presence of two configurations with high travel intention. The causal conditions configuration presented in this study demonstrated the interdimensional relationship between SMIs (attractiveness, similarity, and expertise), trust, and parasocial interaction in terms of travel intention. This study also achieved theoretical contributions and managerial implications on how scholars and tourism managers leverage SMIs to create high travel intentions. Doi: 10.28991/ESJ-2023-07-01-02 Full Text: PDF